Curcuma zedoaria Extract as a Potential Protective Agent against Doxorubicin-Induced Toxicities in Rats - Sumarheni , Sumarheni; Jauhari, Jauhari; Sam, Anwar; Manggau, Marianti A.; Nursyamsi, Nursyamsi; Aswad, Muhammad; Sartini, Sartini (Iranian Journal of Pharmaceutical Sciences, 2023)
DOX therapy as an anticancer agent by incorporation of either physical treatments or antioxidant supplementation. Curcuma zedoaria (Rosc) (family Zingiberaceae) is an indigenous plant with antioxidant and anticarcinogenic activity. This study investigates the potential protective activities of an ethanol extract from Curcuma zedoaria (CZE) against DOX toxicities on non-target organs. A total of 50 female Wistar rats were divided into five groups: control group (G1), DOX only (G2), CZE 350 mg/kg + DOX (G3), CZE 525 mg/kg + DOX (G4), and Vit E + DOX (G5). Daily administration of CZE was given intra-gastric for 30 days, while 5 mg/kg DOX was injected concomitantly each on days 7, 14, and 21. The results of blood biochemical analysis indicated that administration of either the single or multiple doses of DOX (G2) caused significant elevation in the blood levels of alanine aminotransferase (ALT), aminotransferase (AST), creatinine, and CK-MB, indicating that the tissue damages occurred in the liver, kidney, and heart. Treatments with CZE demonstrated that ALT, AST, creatinine, and CK-MB levels remained similar to baseline levels, or no elevation was observed in all groups (G3 and G4). The oral administration of CZE in doses of 350 mg/kg and 525 mg/kg also decreased the AST/ALT ratio independent of the dose given. However, 350 mg/kg CZE indicated a faster response to protecting activities than other treatments. In conclusion, administration of a Curcuma zedoaria (Berg.) Roscoe ethanol extract, particularly in the 350 mg/kg dose, can potentially prevent or reduce DOX's toxicities in the liver, kidney, and cardiac cells.